Hollow Mesoporous Silica Supported Ruthenium Nanoparticles: A Highly Active and Reusable Catalyst for H2 Generation from the Hydrolysis of NaBH4. (1st October 2015) - Peng, Shuge; Pan, Bingli; Hao, Haijiao; Zhang, Jun
Abstract : Ru nanoparticles supported on hollow mesoporous silica (HMS), which are prepared via in situ wet chemical reduction, have been investigated as the highly efficient heterogeneous catalyst for H2 generation from the hydrolysis of an alkaline NaBH4 solution. Many techniques, including X-ray diffraction (XRD), transmission electron microscope (TEM), and X-ray photoelectron spectroscopy (XPS), are used to characterize the as-prepared nanocatalyst (Ru/HMS). Factors, such as Ru loadings in HMS, catalyst concentration, and solution temperature, on catalytic property and reutilization are investigated in this work. A rate of H2 generation as high as 18.6 L min −1  g −1 (Ru) using 1 wt% NaBH4 solution containing 3 wt% NaOH and 40 mg of Ru/HMS catalyst can be reached at room temperature. The minimum apparent activation energy ( E a ) of H2 generation, obtained by fitting the curve of E a values versus catalyst amount, is determined to be 46.7 ± 1 kJ/mol. The residual catalytic activity of the repeated Ru/HMS still remains 47.7% after 15 runs, which perhaps results from the incorporation of the residual by-product (NaBO2 ) in the pores of HMS based on the analysis of XPS.